المقاربات التعليمية والنماذج العملية للأنظمة التعليمية في العالم - صالحي, الحسين (University of Eloued جامعة الوادي, 2021)
تشهد العملية التعليمية بصفة عامة والتعليم الجامعي خاصة تجديدا في مجال المعلومات، واكتساب المعارف بفضل الثورة التكنولوجية المعاصرة التي فرضت نفسها كواقع جديد لدى شعوب العالم، وهذا من خلال ما عرفه العالم من تطور خاصة في العقد الأخير من القرن الماضي, فقد أصبح الاعتماد على تكنولوجيا المعلومات في شتى المجالات الاقتصادية، الثقافية، السياسية والتعليمة بما في ذلك التعليم العالي حتمية وضرورة اجتماعية, مما زاد من مسؤولية القائمين على العملية التعليمية، في ظل الرقمنة وكل هذه التقنيات الجديدة والمتجددة باستمرار. الكلمات المفتاحية: المقاربات التعليمية, النماذج العملية, الأنظمة التعليمية. Abstract: The educational process in general and university education in particular is witnessing a renewal in the field of information, and knowledge acquisition thanks to the contemporary technological revolution that has imposed itself as a new reality among the peoples of the world, and this is through what the world has known of the development, especially in the last decade of the last century. Reliance on information technology in various economic, cultural, political and educational fields, including higher education, has become an imperative and a social necessity, which increases the responsibility of those in charge of the educational process, in light of digitalization and all these new and constantly renewed technologies key words: Educational approaches, practical models, educational systems
مقال